AN ANALYSIS OF ORAL TRADITION AS A HISTORICAL SOURCE - Mandey, Josepha C.; Luntungan, Grace; Iroth, Santje (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to investigate the role of oral tradition as a significant source in reconstructing history. The research method used is a literature study, with reference to several previous studies that mainly focused on collecting data from libraries and previous research. The results of this study are intended to provide an overview and description of the facts, nature, and relationships between phenomena that occur. The use of oral tradition as a historical source provides a valuable alternative, although there are indeed weaknesses and limitations in its verification capacity. Oral tradition is not only limited to the oral dimension, but also includes forms and patterns of oral communication. It became an integral part of the culture and had links to local history. One strategy to utilize oral tradition as a source of local history is to record it through interview techniques and document it in the form of sound or written recordings. Such interview notes and voice recordings can be integrated as part of a document that can be analyzed with the support of other reference materials. The importance of oral tradition in local history is not only limited to cultural value, but also can create economic value for the community in this era.